European Union Policy-Making: The Regulatory Shift in Natural Gas Market Policy - Herweg, Nicole (Palgrave Macmillan, 2017)
‘This book should be read as a benchmark theory building application of the multiple streams approach (MSA) that--through careful development and assessment of hypotheses--demonstrates precisely how MSA can be mapped onto a European context. No doubt policy scholars, advocates, and analysts will find its contents useful for years to come. ' - Michael D. Jones, Oregon State University, USA ‘This book offers a theoretical advancement of the multiple streams approach, which is empirically illustrated by the case of European energy policy. Well-structured and thoughtfully designed and implemented, it will appeal to both emerging and advanced scholars in the fields of comparative public policy, energy politics, and European integration.' - Jale Tosun, Heidelberg University, Germany ‘An important contribution to public policy and a lucid piece of scholarly work. Tracing causal mechanisms of timing and duration in agenda setting and policy change, the book breaks new ground by adapting and systematically applying the multiple streams approach to the European Union’s natural gas sector.' - Nikolaos Zahariadis, Mertie Buckman Professor, Rhodes College, Memphis, USA This book furthers the ongoing theoretical development of the multiple streams framework, assessing its applicability to European Union (EU) policy-making processes. It systematically defines and identifies functional equivalents for all of the framework’s core concepts at the EU level and extends the framework in order to explain agenda-setting and decision-making. Furthermore, the book derives a set of explicit hypotheses to empirically assess the extent to which the (modified) framework is able to explain timing, agenda prominence, and policy change (or a lack thereof) for the EU natural gas directives passed in 1998, 2003, and 2009. The analysis documents that the framework is well-suited to explain the EU policy process in general and reveals where additional theoretical refinements are required. < Nicole Herweg is a postdoctoral researcher at the Institute of Political Science at Heidelberg University, Germany. Her primary field of interest is comparative public-policy analysis, in particular European Union energy policy. She has published in leading political science journals, including European Journal of Political Research, Policy Studies Journal, and Policy Sciences
Keywords: Hochschulschrift; Politisches System; Gasversorgung; Energiepolitik; Europäische Union